ANALISIS KONSEP JUAL BELI DALAM ISLAM PADA TRANSAKSI JUAL BELI DROPSHIPPING - Permatasari, Anggun (IAIN Parepare, 2024)
Dropshipping is one of the more popular online business models today. In this system, the seller does not have goods in stock and only acts as an intermediary between the buyer and the supplier. Dropshipping transactions often raise questions about their validity in Islam because the seller does not have ownership of the goods being sold. This study aims to analyze the concept of buying and selling in Islam in dropshipping transactions. The method used is a literature study with a qualitative approach. The results show that dropshipping is basically allowed in Islam as long as it fulfills the pillars and conditions of buying and selling, and does not contain elements of gharar (uncertainty), riba (excess), and tadlis (fraud). However, dropshipping also has the potential to contain elements of gharar (uncertainty) and haram if not done properly. Therefore, it is important for dropshippers to understand sharia principles and apply them in their business practices.